Experimental analysis of Shape-Stabilized PCM applied to a Direct-Absorption evacuated tube solar collector exploiting sodium acetate trihydrate and graphite. (1st October 2022) - Sadeghi, Gholamabbas; Mehrali, Mohammad; Shahi, Mina; Brem, Gerrit; mahmoudi, amirhoushang
Highlights: Single-unit integration of a transparent evacuated tube solar collector with PCM. Employing a shape-stabilized PCM to avoid leakage problem in solar water heaters. Evaluation of various PCM components to reach the optimum heat capacity. Testing different water flow rates to obtain a better discharge efficiency. Generalizing the solar-storage system to meet the hot water demand of a family. Abstract: A problematic issue with the solar water heaters is the storage tank requirement, which takes considerable space and makes the piping and installation more difficult. This study is the first report on experimentally applying a shape-stabilized PCM to a tankless direct-absorption evacuated tube solar collector to address this challenge and directly store solar energy. The proposed salt hydrate PCM was synthesized at various concentrations of related components and after detecting the optimum compound, it was tested under several cycles to ensure its sustainable heat storage capability. Furthermore, after charging the solar system in the stagnation mode (without water flow), it was discharged at 10, 27, and 40 L per hour (LPH) flow rates. It was revealed that the thermal efficiency in the stagnation mode was improved from 66 % to 82 % using this collector-storage system. In addition, it was concluded that changing the flow rate from 10 to 27 LPH does not considerably reduce the heat gain of collector; however, using the flow rate of 40 LPH plunges the discharge efficiency. Ultimately, cost and carbon footprint analyses of the proposed system were conducted and a payback period of 6 years and annual reduction of 5.4 tons of CO2 emissions were reported.